Joint consensus statement on the vaccination of adult and paediatric haematopoietic stem cell transplant recipients: Prepared on behalf of the British society of blood and marrow transplantation and cellular therapy (BSBMTCT), the Children's cancer and Leukaemia Group (CCLG), and British Infection Association (BIA). Issue 1 (January 2023) - Miller, PDE; Patel, SR; Skinner, R; Dignan, F; Richter, A; Jeffery, K; Khan, A; Heath, PT; Clark, A; Orchard, K; Snowden, JA; de Silva, TI
Summary: Haematopoietic stem cell transplant (HSCT) recipients have deficiencies in their adaptive immunity against vaccine preventable diseases. National and International guidance recommends that HSCT recipients are considered 'never vaccinated' and offered a comprehensive course of revaccination. This position statement aims to draw upon the current evidence base and existing guidelines, and align this with national vaccine availability and licensing considerations in order to recommend a pragmatic and standardised re-vaccination schedule for adult and paediatric HSCT recipients in the UK.